Asymmetrical Charge Distribution Over the Strained Silicon Membrane - Lamichhane, Shobha Kanta (Scientific World, 2013)
Scientific World, Vol. 11, No. 11, July 2013, page 17-24 DOI: http://dx.doi.org/10.3126/sw.v11i11.8547